Shaping up the company's internal investment fund through separation portfolios - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2010)
This research paper sets forth that an alternative for managing the internal investment fund of any company, lies on separation portfolios. Firstly, the company's internal investment portfolio is built up within the context of the incremental cash-flow model. Next, separation portfolios are introduced and consequential features for this paper are predicated upon them: firstly, they provide an easier framework for risk-management; secondly, their risk-return profile bring about a down-to-earth performance benchmark. Afterwards, the internal investment portfolio is mapped out like a distinctive separation portfolio. Lastly, pragmatic consequences and some corporate governance advantages of this financial engineering will follow.
Keywords: G11; G34; G32; 330; separation portfolios; portfolio management; incremental cash-flow model; corporate governance; internal investment fund; risk metrics